A CRITICALITY OF THORIUM FUEL IN FAST REACTORS NUCLEAR POWER PLANT - Sari Novalianda; Dwiyanto Dwiyanto; Andri Ramadhan (CERED Indonesia Institute, 2021)
Nuclear energy is an alternative energy that has advantages in the amount of energy it produces, the fuel it uses, and does not produce air pollution. Thorium is one of the fertile nuclear fuels which is abundant, which is four times more than the amount of uranium. Calculation of criticality of fast reactor design using thorium nitride (ThN) fuel using a set of SRAC programs that produce critical conditions for the enrichment of uranium-233 by 5% with excess reactivity value of 0.044% in volume fraction of 65% fuel, 10% cladding and 25% coolant. Thorium fuel can be used as nuclear fuel for nuclear power plants with a burnup time of 50 years.